Deteksi Protein 270 kDa Plasmodium falciparum Isolat Malang pada Membran Eritrosit Penderita Malaria dengan Komplikasi - Dewi Indiastari; Sri Winarsih; Loeki Enggar Fitri (Pustaka Kesehatan, 2018)
Erythrocyte which is infected by Plasmodium falciparum will have various changes on its architecture, affinity, and biomolecular. Beside that, the infected erythrocyte also forms a knob at its surface. This knob are contained with various parasite proteins, one of them is Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP-1). Our previous study had been identified a protein with molecular weight 270 kDa at P. falciparum infected erythrocyte from Malang isolate that was playing a role in cytoadherence process. The aim of this study was to detect the possibility of 270 kDa protein expression at complicated malaria falciparum patient erythrocyte membrane. The method that used was immunocytochemistry with polyclonal antibody to 270 kDa protein. The results showed that two (2) erythrocyte samples from healthy people as control had negative reaction, and so did with five (5) erythrocyte samples of uncomplicated malaria patient, but there was positive reaction that shown at two (2) samples of complicated malaria patient erythrocyte. It can be concluded from the results that 270 kDa membrane protein of P. falciparum infected erythrocyte in complicated malaria patient might be a PfEMP-1. This protein can be detected by immunocytochemistry method using polyclonal antibody and can be used for the candidate of complicated malaria diagnostic Keywords: Plasmodium falciparum, 270 kDA protein, immunocytochemistry, polyclonal antibody